Alleviation of bone markers in rats induced nano-zinc oxide by qurecetin and α-lipolic acid. (21st November 2016) - Abdelkarem, Hala M.; Fadda, Laila M.; Kaml, Omyma R.
Abstract: The purpose of this study was to evaluate the potential protective effect of qurecetin (Qur) and α-lipolic acid (ALA) to modulate the perturbation of bone turnover which is induced by nano-zinc oxide (n-ZnO). Rats were fasted overnight and randomly divided into two groups: G1, normal healthy animals and the other rats were administered zinc oxide nanoparticles orally by guava in a dose of 600 mg/kg body weight/d for 5 sequential days in Wistar albino male rats. N-ZnO-exposed animals were randomly sub-divided into three groups: G2, n-ZnO-exposed animals; G3, n-ZnO-exposed animals co-treated with Qur (200 mg/kg daily); and G4, n-ZnO-exposed animals co-treated with ALA (200 mg/kg). Qur and ALA were administered orally by guava daily for three sequential weeks from the beginning of the experiment. The results revealed a significant reduction of nitiric oxide (NO) and serum level and comet assay in n-ZnO exposure rats after treatment of Qur and ALA. It was found the alteration of pro-inflammatory markers (tumor necrosis factor alpha; TNF-α, interleukin-6; IL-6 and C-reactive protein; CRP), bone alkaline phosphatase (B-ALP, bone formation marker), and C-terminal peptide type I collagen (CTx, bone resorption marker) levels compared with the normal group. Co-administration of Qur and ALA in n-ZnO-exposed rats significantly alleviated the mentioned alterations of biochemical parameters. These results suggest that Qur and ALA as antioxidant agents may be a candidate for preventive and treatment applications of impaired bone markers induced bone loss caused by nano-particles of metal oxide.